2009
DOI: 10.1111/j.1743-6109.2008.01112.x
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous Artery Intima-Media Thickness: A New Parameter in the Diagnosis of Vascular Erectile Dysfunction

Abstract: Introduction A precise characterization of erectile dysfunction (ED) of vascular origin has not yet been achieved. Although cavernous peak systolic velocity (PSV) is generally considered a major parameter, it has many false positives and negatives because of anatomic variations of the cavernous artery course, challenging site of sampling, insufficient caracterization of an early phase of vascular disease, and significant influence of adrenergic tone. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 22 publications
(29 reference statements)
2
41
0
2
Order By: Relevance
“…Carotid IMT may not completely reflect the structural status of such a distant and small vessel-like cavernosal artery. The study of Caretta et al, 16 in which femoral IMT was also measured besides carotid and cavernosal IMT, have shown that femoral IMT was superior to carotid IMT for identifying patients with peripheral vascular disease. In addition, they have found that there is a higher prevalence of atherosclerotic lesions at femoral site.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Carotid IMT may not completely reflect the structural status of such a distant and small vessel-like cavernosal artery. The study of Caretta et al, 16 in which femoral IMT was also measured besides carotid and cavernosal IMT, have shown that femoral IMT was superior to carotid IMT for identifying patients with peripheral vascular disease. In addition, they have found that there is a higher prevalence of atherosclerotic lesions at femoral site.…”
Section: Discussionmentioning
confidence: 99%
“…However, we do not know what percentage of that group with increased carotid IMT had pathologically increased cavernosal IMT. In their report, Caretta et al 16 used a cutoff level of 0.3 mm for cavernosal IMT and found that there was a linear positive correlation between cavernosal, carotid and femoral IMT. Our patient population was not enough for making such a classification.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations